EphA4 promotes cell proliferation and cell adhesion–mediated drug resistance via the AKT pathway in multiple myeloma. Issue 3 (March 2017) - Ding, Linlin; Shen, Yaodong; Ni, Jing; Ou, Yiqing; Ou, Yangyu; Liu, Hong
Eph receptor A4 (EphA4), a member of the erythropoietin-producing hepatocellular (Eph) family, has been reported to upregulate in several tumors. However, the role of EphA4 in multiple myeloma has not been clarified yet. In this study, we found that EphA4 promoted proliferation of multiple myeloma cells via the regulation of cell cycle. Besides, EphA4 was closely related to cell adhesion of multiple myeloma cells and promoted cell adhesion–mediated drug resistance by enhancing the phosphorylation levels of Akt (p-AKT) expression in multiple myeloma. More interestingly, we discovered that EphA4 can interact with cyclin-dependent kinase 5 (CDK5) and regulate its expression in multiple myeloma. CDK5 has been reported to be overexpressed in multiple myeloma which mediated bortezomib resistance and also participated in AKT pathway. And we have also proved the fact. So, we supposed that EphA4 interacted with CDK5 and promoted its expression which in turn enhanced p-AKT expression and promoted cell adhesion–mediated drug resistance in multiple myeloma. Therefore, this study clarifies the molecular mechanism of cell adhesion–mediated drug resistance and may be useful in identifying potential target for treatment of multiple myeloma.